Overcurrent time delay determination using gain scheduled PID controllers - Zainul A.A.; Ramasamy A.; Abidin I.Z.; Nagi F.H. (2023)
The inverse time overcurrent relay operation is based upon the current setpoint and also the time multiplier setting. Depending on the ratio of the value of the current and the setpoint current together with the value of the time multiplier setting, the amount of time delay for the trip command is determined using the inverse time characteristics. This would mean that the relay is not of the adaptive type and would possibly give a maltripping. This paper uses the concept of PID controller to determine the time delay for the overcurrent relay. 2009 IEEE.